Konsep Taubat Tarekat NaqshabandÃ®yah MuzharÃ®yah - Hoddin, M. Sholeh (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2012)
Sufism which was originally the activities of individuals to get closer to Allah has become an institution of tarekat in its development and has rules and procedures for the dhikr or wird. Among the growing tarekat in the history of Islam is tarekat Naqshbandiyya Muzhariyya. As the Sufi orders, this tarekat has rules or procedures that must be obeyed by its adherents. Therefore, before proceeding to higher levels (maqâmât) in the tarekat, a disciple has to step on the very bottom of tarekat ladder, namely repentance. The repentance has substantial roots, i.e. takhallî and tahallî. The article was presented as a form of conceptual understanding of the meaning of repentance for the tarekat Naqshbandiyya Muzhar-iyya. Repentance, according to Naqshbandiyya Muzhariyya Ghersempal, is the beginning of all maqâms and hals. It is also considered the first maqâm for the followers of this tarekat after their return from disgraceful deeds to noble conducts. During repentance process a disciple must undergo a number of rituals, namely bay?ah, tawajjuh, Rabita, khatm khajagan, and dhikr.